The influence of hostel lifestyle in shaping the dicipline of the students of SMK Seksyen 11 Shah Alam Selangor / Muhamad Azamuddin Ahmat Miskam - Ahmat Miskam, Muhamad Azamuddin (Faculty of Education, 2014)
This research was conducted to evaluate the influence level of hostel lifestyle in developing student’s discipline. The factors which influence student’s discipline are peers, hostel’s management and rule regulations, and hostel’s activities. The research involved 40 form five students’ at Sekolah Menengah Kebangsaan Seksyen 11, Shah Alam Selangor. A set of questionnaire was carried out to gain the information on the research topic. The data was analyzed by using “Statistical Package for the social Science Version 22.0. Descriptive quantitative analysis in a form of frequency and percentages is used in data analysis process. For the overall result the research shows that the influences level of peers and hostel’s activities at the high level influence development student’s discipline in hostel while the influences level of hostel’s management and rule regulation at the moderate level.